2022
DOI: 10.1111/cns.13877
|View full text |Cite
|
Sign up to set email alerts
|

Gray and white matter alterations in different predominant side and type of motor symptom in Parkinson's disease

Abstract: Background: Parkinson's disease (PD) is highly heterogeneous reflected by different affected side of body and type of motor symptom. We aim to explore clinical characteristics and underlying brain structure alterations in PD with different predominant sides and motor types. Methods: We recruited 161 PD patients and 50 healthy controls (HC). Patients were classified into four subtypes according to their predominant side and motor type: left akinetic/rigid-dominant (LAR), left tremor-dominant (LTD), right akinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Tract-Based Spatial Statistics (TBSS) is a popular automated approach to co-register individual DTI maps to the common DTI skeleton maps that allow statistical and objective group comparisons only on the voxels in the skeletonized white matter tracts (Smith et al, 2006). To date, TBSS is one of the most popular DTI analytic methods to investigate DTI changes due to PD with different neurodegenerative conditions (Wen et al, 2018;Ji et al, 2019;Chen et al, 2022). Unlike VBA investigating the overall diffusivity or anisotropy of a voxel, a fixelbased analysis is more likely to quantify the intravoxel white matter properties with the exclusion of other tissue compartments.…”
Section: Recent Advances In Diffusion Tensor Imaging Analytic Methodsmentioning
confidence: 99%
“…Tract-Based Spatial Statistics (TBSS) is a popular automated approach to co-register individual DTI maps to the common DTI skeleton maps that allow statistical and objective group comparisons only on the voxels in the skeletonized white matter tracts (Smith et al, 2006). To date, TBSS is one of the most popular DTI analytic methods to investigate DTI changes due to PD with different neurodegenerative conditions (Wen et al, 2018;Ji et al, 2019;Chen et al, 2022). Unlike VBA investigating the overall diffusivity or anisotropy of a voxel, a fixelbased analysis is more likely to quantify the intravoxel white matter properties with the exclusion of other tissue compartments.…”
Section: Recent Advances In Diffusion Tensor Imaging Analytic Methodsmentioning
confidence: 99%
“…In addition, right fusiform gyrus has also shown greater grey matter loss in PD patients with psychosis compared to those without psychosis [64]. Cingulate gyrus, another common hub in PD subtypes B and AB, is associated with cognitive functions and non-motor symptoms in PD [65,66]. Since right fusiform gyrus is detected as a conserved hub in subtypes A and B and left cingulate gyrus in subtypes B and AB, we suggest these nodes may play a crucial role in keeping the communication active in PD subtypes, and hence, may further be investigated to understand the disease pathophysiology.…”
Section: Network Analysismentioning
confidence: 98%
“…In comparison to healthy controls (HC), most studies found degeneration in PD patients with motor symptoms, as indicated by decreased FA [ 37 , 79 , 83 ], increased MD [ 74 ] and a combination of decreased FA and increased MD [ 46 ]. These results suggest that FA, MD, and other DTI measures could serve as quantitative biomarkers of motor symptom severity in PD.…”
Section: Cingulummentioning
confidence: 99%
“…Depression and dementia frequently occur in PD patients, often appearing late in the disease at stage 3 or 4 of the Hoen and Yahr staging for motor involvement. They can also be present early on in the honeymoon period of PD, and have been shown to correlate with the severity of motor involvement [ 37 ]. Abnormal functioning in depression and dementia in PD patients may be due to degeneration of the microstructure in the white matter located in frontal-limbic regions.…”
Section: Cingulummentioning
confidence: 99%